Drought decreases annual streamflow response to precipitation, especially in arid regions - A. Matanó; R. Hamed; M. I. Brunner; M. I. Brunner; M. I. Brunner; M. H. Barendrecht; A. F. Van Loon (Hydrology and Earth System Sciences, 2025)
Persistent drought conditions may alter catchment response to precipitation, both during and after the drought period, hindering accurate streamflow forecasting of high flows and floods. Yet, the influence of drought characteristics on the catchment response to precipitation remains unclear. In this study, we use a comprehensive dataset of global observations of streamflow and remotely sensed precipitation, soil moisture, total water storage, and normalized difference vegetation index (NDVI). Using multivariate statistics on 4487 catchments with a stationary annual streamflow–precipitation ratio, we investigate the influence of drought on fluctuations of streamflow response to precipitation. Our analysis shows that, generally, droughts with streamflow or soil moisture anomalies below the 15th percentile lead to around 20 % decrease in streamflow response to precipitation during drought compared to the historical norm. However, this decrease is reduced to only about 2 % 1 year after the drought, which suggests a generally low influence of preceding drought conditions. These effects are more pronounced when droughts are longer and more severe. Most changes were found in arid and warm-temperate regions, whereas snow-influenced regions exhibit fewer changes in catchment response due to drought. In addition, we used step change analyses on 1107 catchments with non-stationary annual streamflow–precipitation ratios to identify significant abrupt shifts in the time series, examining the role of drought in driving these shifts. This analysis revealed both positive and negative shifts in annual streamflow response to precipitation after severe and persistent drought conditions regardless of climate and catchment characteristics. Positive shifts occur only when the drought propagated through the hydrological system after extended dry periods, while negative shifts are usually linked to shorter, intense dry periods. This study sheds light on the importance of considering climate characteristics in predicting dynamic catchment response to precipitation during and after persistent drought conditions.